Evapotranspiration Partitioning Across US Ecoregions: A Multi‐Site Study Using Field Stable‐Isotope Observations - Katarena A. Matos; Gabriel J. Bowen; Stephen P. Good; Scott T. Allen (Geophysical Research Letters)
Abstract Quantifying relative contributions of plant transpiration (T) and soil evaporation to evapotranspiration (ET) is crucial to better understand how vegetation influences and controls ET, the largest efflux of the terrestrial water balance. Here, we derive estimates of transpiration fraction (T/ET) using consistent isotope‐based ET partitioning methods for 13 sites spanning five ecosystem types of the continental US, capturing 56 snapshots of T/ET during the growing season. We found transpiration dominated the ET flux across all sites with a mean T/ET of 0.81 ± 0.08 (±standard error). Sites and dates with higher vegetation indices exhibited higher T/ET and transpiration rates, with the latter increasing 0.30 mm/day per unit Leaf Area Index and 2.9 mm/day per unit Normalized Difference Vegetation Index. Counter to expectations, antecedent precipitation had no effect on T/ET. Despite the breadth of ecosystems and conditions represented, evaporation exceeded transpiration only once, suggesting that evaporation rarely dominates ET in the growing season.